The Decision Of The Aceh Community To Invest In Sharia - Harjoni Desky; Husni Mubarrak (International Journal of Management and Business Economics, 2022)
Society and investors have a valuable role in the sharia capital market. For that, an analysis effort on community decisions is needed. This study analyzes the factors influencing people's decisions through perceptions, motivation, and learning. This research will use the consumer decision-making process model then replication by entering the knowledge variable as a substitute for learning in the model. This research is a type of survey research using a purposive sampling technique with 160 respondents. For data analysis techniques, the sed Structural Equation Modeling (SEM) approach with the help of Amos Version 24.0. The results show; that first, knowledge of sharia investment has a positive relationship with the perception of investing Shariah with a value ratio (CR) of 2.618; secondly, perception is positively related to motivation to invest Sharia, with its critical ratio value (CR) of 5,200; third, the motivation variable is positively related to the decision to invest Sharia, with its critical value (CR) of 2.052; the knowledge of sharia investment products is positively associated with the decision to invest in Sharia, as evidenced by the value of the critical ratio (CR) of 1.977. Fifth, perception has no relation with the decision to invest in Sharia because the value of the critical ratio (CR) of 0,430 is under requirement CR> 1,96, so the alternative hypothesis (HA) is rejected. The results of this study reinforce the importance of efforts to increase public knowledge of sharia investment products and the ins and outs of Sharia.